Experimental investigation of the effects of temperature on the morphological characteristics of geopolymer binders - Suppiah, R.R. (Springer Science and Business Media Deutschland GmbH, 2022)
Since the beginning of this century, assessment of the environmental impacts and the global warming potential of industrial practices and technologies are on the top agenda. Therefore, many construction materials such as cement systems are being designed for reducing the environmental impacts and greenhouse gas emissions. For that purpose, the petroleum industry is also striving for developing environmentally friendly cementing systems for oil well application; for example, a better alternative to the class-G cement, which is consumed in a tremendous amount worldwide. In finding the greener alternative to class-G cement, geopolymer binders are being researched for possible applications for oil-well cementing jobs. This paper presents the experimental investigation of the effects of temperature on the morphological characteristics of geopolymer binders. For that purpose, sodium silicate and sodium hydroxide were used as the alkaline activator with fly ash as the precursor. Fifteen samples were prepared with a density of 10, 11, 13, 15 and 17Â ppg (3 samples for each value of density). The samples were subjected to a temperature of 30, 60, and 90Â Â°C and cured in a water bath for 24Â h. Morphological and microstructural characteristics were analyzed using XRD and FESEM. In an overview, increases in temperature significantly impact the geopolymerization process where the microstructure in geopolymer cement produces more reacted particles, which results in excellent mechanical strength. Generally, the strength of geopolymers is associated with the fly ash dissolution FESEM image for 17Â ppg mixture cured at 90Â Â°C clearly shows that it underwent extensive geopolymerization with the formation of continuous alumino-silicate gel and almost entirely reacted fly ash particles, resulting in relatively dense geopolymer matrix. Â© 2022, The Author(s).